Aortic Root Rupture during Transcatheter Aortic Valve Implantation in a Patient with Idiopathic Thrombocytopenic Purpura: Utility of Transesophageal Echocardiography in Early Detection and Description of a Semiconservative Surgical Management Approach - Chandrasekhar, Jaya; Ruel, Marc; Nicholson, Donna; Labinaz, Marino (International Journal of Angiology, 2016)
An 87-year-old man with idiopathic thrombocytopenic purpura and platelet count of 56 × 109/L underwent transesophageal echocardiography (TEE)–guided transcatheter aortic valve implantation using a femoral approach. Post valve deployment, a new pericardial effusion was noted which was successfully drained. Despite this, the patient became hypotensive needing vasopressor support with reaccumulation of pericardial fluid. Emergent sternotomy was performed and a perforation of the right ventricular apex was noted which was sealed with a pledgeted suture. Continued bleeding prompted further exploration; the aorta was seen to be mottled in conjunction with clear aortic root hematoma on TEE and a diagnosis of root rupture was made. This was semiconservatively managed without conversion to a full aortic root repair or replacement procedure. Multiple sutures were applied to the periaortic space and the bleeding sealed with use of BioGlue (Cryolife Inc., Kennesaw, GA) and Surgicel (Ethicon Inc., Somerville, NJ). The postoperative course was stable and the patient remained well at 3-month follow-up.
Keywords: aortic valve stenosis; percutaneous aortic valve replacement; emergent sternotomy; surgical conversion; pericardiocentesis